Humanimal Methods and Methodologies: Review of Lynda Birke and Jo Hockenhull, Crossing Boundaries: Investigating Human-Animal Relationships - Bull, Jacob (Humanimalia, 2015)
Lynda Birke and Jo Hockenhull. Crossing Boundaries: Investigating Human-Animal Relationships. Leiden: Brill, 2012. 255 pp. €95.00; $124.00.